The Propeller Myocutaneous Flap of the Upper Eyelid: Anatomical Study and its Clinical Implication. Issue 7 (12th October 2021) - Delia, Gabriele; Fazio, Antonina; Parafioriti, Andrea; Meduri, Alessandro; Inferrera, Leandro; Stagno d'Alcontres, Francesco
Abstract : Background: The reconstruction of the upper eyelid and the periorbital region is a challenge for the surgeon. The aims of this reconstruction are to guarantee protection to the eyeball, maintain the visual field, and restore the function of the eyelid without damaging other anatomical structures. In this study, the authors describe the use of a propeller myocutaneous flap based on the small vertical branches of marginal, peripheral ed superficial arcade, for the reconstruction of the upper eyelid or periorbital region. Materials and Methods: The authors enrolled 3 patients (Caucasian), between 2018 and 2019, and subjected to reconstructive surgery with the propeller myocutaneous flap of the periorbital region at the Plastic Surgery Unit of the University of Messina. The vascularization of the flap was demonstrated through an anatomical study conducted on cadavers at the dissection laboratories of the University of Bordeaux 2. Results: The authors have shown that the myocutaneous flap represents a valid alternative for loss of substance coverage and reconstruction of the upper eyelid or periorbital region, allowing the achievement of a good aesthetic and functional result. Follow up: Patients were followed up at 3–6–12 months. No complications were reported (flap retraction, periocular region deformity, donor site morbidity). Furthermore, at the last visit, the scars were almost invisible. Conclusions: The use of the propeller myocutaneous flap of the upper eyelid is a valid reconstructive alternative to the standard techniques described so far for the reconstruction of the periorbital region.